PENGEMBANGAN KREATIVITAS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN MENGGAMBAR BEBAS DI TK NEGERI PEMBINA 3 RANTAU PANJANG KECAMATAN TABIR - Ramuna; Atika Wirdasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop the creativity of children aged 5-6 years through drawing activities at Taman Kanak-Kanak Negeri Pembina 3 Rantau Panjang, Kecamatan Tabir, Kabupaten Merangin. Drawing activities are considered important as they can enhance creativity, fine motor skills, and self-expression in children. However, at Taman Kanak-Kanak Negeri Pembina 3 Rantau Panjang, drawing activities have not been fully developed, with many children struggling to express their ideas. This research uses a qualitative approach with a descriptive method, combining triangulation data collection techniques: observation, in-depth interviews, and documentation. The research subjects consist of 15 children selected using purposive sampling. The collected data were analyzed inductively to explore the implementation, barriers, and efforts to develop creativity through drawing activities. This study is expected to contribute to the development of art learning programs, especially drawing, in early childhood education institutions, as well as provide insights for teachers and parents in supporting children's creativity.